2017
DOI: 10.1051/epjconf/201715703029
|View full text |Cite
|
Sign up to set email alerts
|

Sawtooth pacing with on-axis ICRH modulation in JET-ILW

Abstract: Abstract.A novel technique for sawteeth control in tokamak plasmas using ion-cyclotron resonance heating (ICRH) has been developed in the JET-ILW tokamak [2]. Unlike previous ICRH methods, which explored the destabilization of the internal kink mode when the radiofrequency (RF) wave absorption was placed near the q=1 surface, the technique presented here consists of stabilizing the sawteeth as fast as possible by applying the ICRH power centrally and inducing a sawtooth crash by switching it off at the appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A second typology of test has been performed, aimed at investigating the causality horizon [ 26 , 27 , 28 , 29 ], i.e., the maximum time interval into which two physical quantities are synchronized and in which one observable can be thought as the “drive mechanism” of the second observable, for periodic and quasiperiodic signals of the same nature as those encountered in real experiments in thermonuclear scenarios [ 30 , 31 ]. In this kind of experiment, particular instabilities of the plasma, with potential harmful effects on the machine integrity, are paced by triggering them frequently enough that they do not have time to become dangerous for either the performance or safety of the reactor.…”
Section: Numerical Tests: Causality Horizonmentioning
confidence: 99%
See 2 more Smart Citations
“…A second typology of test has been performed, aimed at investigating the causality horizon [ 26 , 27 , 28 , 29 ], i.e., the maximum time interval into which two physical quantities are synchronized and in which one observable can be thought as the “drive mechanism” of the second observable, for periodic and quasiperiodic signals of the same nature as those encountered in real experiments in thermonuclear scenarios [ 30 , 31 ]. In this kind of experiment, particular instabilities of the plasma, with potential harmful effects on the machine integrity, are paced by triggering them frequently enough that they do not have time to become dangerous for either the performance or safety of the reactor.…”
Section: Numerical Tests: Causality Horizonmentioning
confidence: 99%
“…Besides practical implementation difficulties, the evaluation of the pacing efficiency is difficult because the instabilities are quasi periodic, and therefore after a perturbation induced by the control systems, if enough time is allowed to pass, they are bound to reoccur. Typical pacing techniques are the injection of frozen deuterium pellets for controlling ELM instabilities [ 31 ] or ICRH power modulation for the control of sawtooth instabilities [ 30 ]. The latter experiment has been considered in this paper, by means of a simple synthetic model.…”
Section: Numerical Tests: Causality Horizonmentioning
confidence: 99%
See 1 more Smart Citation
“…A need for control of the sawtooth instability is also anticipated in ITER, in order to avoid long period sawteeth with large amplitude crashes that could trigger an NTM instability [23], and several schemes using ECCD or ICRF heating have been proposed [24]. Recent JET experiments have shown that the sawtooth period can be controlled with low field side ICRF heating (as will be available in ITER) near the q=1 surface [25], and that sawtooth pacing can be achieved with modulated central ion cyclotron heating [26], a method that is less sensitive to the deposition location. Further work is needed to validate ICRF sawtooth control in ITER-relevant H-mode discharges.…”
Section: Plasma Configuration Controlmentioning
confidence: 99%
“…In the case of ELMs, the periodic injection of small frozen pellets of fusion fuel into the plasma edge at high frequency is a very promising solution [ 2 ]. The modulation of the Ion Cyclotron Radiofrequency Heating (ICRH) power has proven to be an efficient solution for sawteeth pacing, reducing the fast ion component, which has a stabilizing effect [ 3 ]. Pellets and ICRH notches represent time localized perturbations of the natural evolution of the plasma, with a clear causal direction.…”
Section: Introductionmentioning
confidence: 99%